Traffic collisions in space: four decades of advancement in applied GIS. Issue 1 (2nd January 2016) - Yao, Shenjun; Loo, Becky P.Y.; Yang, Bruce Zi
Abstract: Traffic collision analysis is essential for reducing traffic injuries. While most traditional approaches focus on the time dimension of traffic collisions, the recent past has witnessed a growing awareness of the spatial dimension in a geographical context. In this paper, 70 studies on the application of GIS to the spatial analysis of traffic collisions are reviewed. The purpose of the paper is to provide a systematic analysis of the major advancements in applied GIS for studying traffic collisions in space since the mid-1970s.